KEEFEKTIFAN TEKNIK STORYBOARD DALAM PEMBELAJARAN KETERAMPILAN BERCERITA SISWA KELAS VII A MTS MUHAMMADYAH LIMBUNG - Kartini Kartini (JURNAL KONFIKS, 2018)
The objective of this research was to describe the effectiveness of storyboard in learning storytelling skill of second year students of class VII A at MTs Muhammadiyah Limbung. This research used descriptive quantitative method with the research design was pre-experimental design. The achievement of students result in learning storytelling had the average (84, 19) of 37 students and all of the student were completed the Kriteria Ketuntasan Minimal (KKM) with the higher score was (90) and the lower score was (75). Since the achievement, (99, 99%) students achieved Kriteria Ketuntasan Minimal (KKM). By using Kolmogorov-Smirnov test, the result of the average score analysis for pre-test shown that Pvalue α was (0, 56) 0, 05 and the average score for post-test shown that Pvalue α was (0, 09) 0, 05. The data shown that the result of pre-test and post-test included in normal category. Based on the result of SPSS analysis, shown that P (sig. (2-tailed) was 0,000 0, 05. It shown that the average of students’ result in learning after taught by using storyboard technique was more than 74, 9. It implied that H0 was rejected and H1 was accepted which implied that the average of students’ result (post-test) of second year students of class VII A MTs Muhammadiyah Limbung. Based on the result of the research above, could be concluded that learning storytelling skill by using storyboard technique was more effective than the conventional method of learning. By using the technique, students’ intellect and grasp skill were more stimulated in telling an event or their experience by using visual aid as the aid in conveying the event or experience.